Project selection for group decision making: a multiple project perspective from Pakistan - Basheer, Muhammad Farhan; Imran, Muhammad; Abdul Hamid, Siti Norasyikin; Aziz, Azelin (Mason Publishing, 2018)
Decision making is one of the primary functions of management. Making strategic decisions are important to achieve organisational efficiency and effectiveness. In the selection of projects, it is necessary for organisations to prioritise their projects due to limited resources. Therefore, the selection of projects that bring value and substantial impact on the organisation is very important to ensure that they can compete in the dynamic external environment and meet the goals and objectives. From the case study, the result suggests that the Analytical Hierarchy Process (AHP) method can contribute significantly to the identification of sources that need further clarification of attributes and criteria and at the same time it can provide a systematic analytical tool in making a group decision. This method allows the organisation to prioritize its projects based on certain criteria as it is a quantitative decision support tool. In conclusion, AHP is the best and efficient method for decision makers to consider all facts, weigh the pluses and minuses, reach, reevaluate and communicate their decisions.